Green epi-endophytes in Hymenena falklandica (Rhodophyta) from the Patagonian coasts of Argentina: Preliminary observations. - Gauna, Maria Cecilia (2008)
The occurrence of epi-endophyte algae in Hymenena falklandica J. G. Ag. Ex Kylin (Rhodophyta) is reported in Argentina. Epicladia heterotricha (Yarish) Nielsen (Chlorophyceae) revealed a 100% prevalence of occurrence, particularly in the basal region of the host. Low (14%), moderate (28%) and high (58%) severity degrees of infection were also registered for E. heterotricha. Pseudendoclonium submarinum Wille (Chlorophyceae) exhibited a lower frequency of occurrence, close to 3%. The developmental morphology and dynamics of E. heterotricha and P. submarinum were investigated under unialgal as well as bialgal culture conditions. The experimental infection of H. falklandica by E. heterotricha demonstrated that E. heterotricha initially behaves as epiphytic but with endophytic filaments growing into the cortex of the host during late infection. P. submarinum was found to be exclusively epiphytic, with no development of endophytic filamentous systems. The present study reports the first lines of evidence of an epidemiological study conducted with the purpose of comparing both the prevalence and effects of algal epi-endophytic organisms in H. falklandica in the southern coasts of Argentina.